The effects of slope shape and polyacrylamide application on runoff, erosion and nutrient loss from hillslopes under simulated rainfall. Issue 4 (12th April 2021) - Ao, Chang; Zeng, Wenzhi; Yang, Peiling; Xing, Weimin; Lei, Guoqing; Wu, Jingwei; Huang, Jiesheng
Abstract: Natural hillslopes are mostly composed of complex slope shapes, which significantly affect soil erosion. However, existing studies have mainly focused on uniform slopes to simplify complex hillslopes, and the mechanisms responsible for the influence of slope shape on soil and nutrient losses are still not well understood, especially in the application of soil improvers to reduce soil loss. To investigate the effects of slope shape and polyacrylamide (PAM) application on runoff, soil erosion and nutrient loss, this study conducted artificial field rainfall experiments involving two PAM application rates and nine slope shapes. The results indicate that the average amount of soil loss from convex slopes was 1.5 and 1.3 times greater than that from concave and uniform slopes, respectively, and the average amount of ammonia nitrogen loss and phosphate loss increased by 24.0%–58.6%. Soil and nutrient losses increased as the convexity of the convex slopes increased. For runoff, there was little difference between concave and convex slopes, but the runoff amount for both slopes was greater than that for uniform slopes. After PAM application, the soil loss decreased by more than 90%, and the nutrient loss decreased by 28.2%–68.1%. The application of PAM was most effective in reducing soil erosion and nutrient loss from convex slopes, and it is recommended to appropriately increase the PAM application rate for convex slopes. A strong linear relationship between ammonia nitrogen and phosphate concentrations and sediment concentrations was found in the runoff on slopes with no PAM application. However, this linear relationship weakened for slopes with PAM application. The findings of this study may be valuable for optimizing nonpoint source pollution management in basins. Abstract : The soil and nutrient loss from hillslope was increased with the increase of the convexity of slope under rainfall, but decreased with the increase of the concavity. Polyacrylamide reduced soil and nutrient loss from hillslope and this effect was performed better on convex slopes. A linear positive correlation was found between the ammonia and phosphate concentration and the sediment rate in runoff.